Postglacial Echoes: Parasite Genomics Uncover Environmental Changes in Postglacial European Lakes - Llaberia-Robledillo, Mar; Lucas-Lledó, José Ignacio; Balbuena, Juan Antonio; Brabec, Jan; Bilat, Julia; Knudsen, Rune; Seehausen, Ole; Blasco-Costa, Isabel (Molecular ecology, 2025)
Postglacial environmental changes have influenced biodiversity and species evolution, yet the genomic and demographic responses of parasites remain underexplored. This study investigates the population genetics and demographic history of the flatworm Phyllodistomum umblae, a generalist trematode at the definitive host level infecting Coregonus spp. across perialpine and subarctic postglacial lakes. Additionally, we compare its demographic patterns to Proteocephalus fallax, a whitefish specialist tapeworm, to elucidate how ecological strategies shape evolutionary responses to environmental fluctuations. Genomic data from ddRAD sequencing revealed clear genetic differentiation in P. umblae between subarctic and perialpine regions, likely driven by geographic isolation during glacial cycles. Low genetic differentiation suggests hydrological connectivity and the parasite's ability to utilise several host species as definitive hosts. Demographic inference uncovered distinct evolutionary trajectories between P. umblae and Pr. fallax. During the Last Glacial Period (~115-11 kya), P. umblae populations underwent declines, followed by rapid postglacial expansions after the Last Glacial Maximum (~15-10 kya). In contrast, Pr. fallax exhibited older historical fluctuations, including pronounced bottlenecks during the Middle Pleistocene (~300 kya). Its populations remained stable during the LGP, likely due to host persistence in glacial refugia unavailable in earlier glaciation periods. These findings align with the taxon pulse concept within the Stockholm Paradigm, highlighting how glacial cycles triggered episodic population contractions and expansions. By integrating genomic and historical data, this study (1) underscores parasites as models for understanding ecological and evolutionary processes and (2) provides insights into biodiversity resilience and adaptation to past and future environmental changes.
Keywords: populační genetika; demographic inference; genetická variace; Genetics, Population; Lakes; Europe; biologická evoluce; Genomics; jezera; Evropa; Animals; ddRAD‐seq; Biological Evolution; zvířata; Trematoda; freshwater; Salmonidae; Genetic Variation; population genetics; genomika